ANALISIS KEBIJAKAN PENYEDIAAN LAHAN BAGI PEMBANGUNAN DENGAN KEWAJIBAN PENANGGULANGAN DAN PENCEGAHAN DINAMIKA TUMBUHAN INVASIF DI INDONESIA - Priyaji Agung Pambudi; Tommy Hendra Purwaka (Universitas Lambung Mangkurat, 2019)
Life on land as one of the goals of sustainable development is an important aspect to be realized. Terrestrial ecosystems become a space for human life to carry out their daily activities. However, along with the high activity of trade, tourism, and development risk of degradation of terrestrial ecosystems is increasing. The introduction of invasive plants as a result of its aspects currently ranks second as the cause of loss of organism species under the main cause of land conversion. This study aims to analyze development policies in terms of handling invasive plants in Indonesia. The study was conducted with a literature review and desk study through a review of laws, government regulations, presidential decrees, and ministerial regulations. Based on the results, it is known that basically, Indonesia does not yet have policies that regulate in detail and detail about invasive alien plants, existing policies only regulate the management and protection of biodiversity. There are 9 documents relating to biodiversity conservation, but no one of these policy documents has touched on clearly and in detail about protecting ecosystems from the threat of invasive alien species. Policies need to be established regarding principle licenses, location permits, business licenses, and trade access permit to suppress and minimize the spread of invasive plants. The thing that needs to be emphasized is the clarity of the policy (legislation) because only through this strategic steps can be done on a clear and strong legal basis.